1981
DOI: 10.1002/bbpc.19810851215
|View full text |Cite
|
Sign up to set email alerts
|

Self Diffusion in Carbon Dioxide Near the Critical Point

Abstract: die Aktivierungsparameter AG* von 2 und 3 erstaunlich gut mit den fur N, N-Dimethylacetamid und Measurements of the self diffusion coefficient, D, by the nuclear-magnetic-resonance field-gradient method for carbon dioxide ('kO,) are reported for the coexisting liquid from the triple point to the critical point and for the fluid at the critical density from the critical temperature upwards. No anomaly in D is observed near the critical point and the behaviour is similar to that of other liquids. It seems like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The diffusion coefficient for liquid carbon dioxide at 30.5°C is ¾5 ð 10 4 cm 2 /s. 15 Therefore, the average displacement of a single molecule during the dephasing time T 2 (¾3 ps) is about 0.2 nm. This value is much less than the NG pore diameter (4 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The diffusion coefficient for liquid carbon dioxide at 30.5°C is ¾5 ð 10 4 cm 2 /s. 15 Therefore, the average displacement of a single molecule during the dephasing time T 2 (¾3 ps) is about 0.2 nm. This value is much less than the NG pore diameter (4 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The self-part of the dynamic structure factor is approximated to be purely diffusive, where D means the self-diffusion coefficient of the solute. We neglect the critical anomaly of the self-diffusion coefficient, because it is quite small if any. , …”
Section: Resultsmentioning
confidence: 99%
“…We neglect the critical anomaly of the self-diffusion coefficient, because it is quite small if any. 31,32 Equations 20 and 21 are substituted into eq 19 to get the final expression as follows:…”
Section: Iiia Static Fluctuationmentioning
confidence: 99%
“…In fact, Duffield and Harris 12 reported a sudden increase of the values of D near the critical temperature. NMR studies by Krynicki et al 13 and by Etesse et al 14 stand in contradiction to the finding of Duffield and Harris and found no anomaly in the behavior of D. Although the values of D given in the two cited papers were measured by the same technique, there is a 40% systematic difference between the two studies. In general, most of the experimental results which were reviewed by Hamann et al 15 indicate that there is no anomaly in the behavior of D in the critical region of systems such as CH 4 , C 2 H 4 , CClF 3 , and SF 6 .…”
Section: Introductionmentioning
confidence: 69%